Appraisal of Inter-Professional Education (IPE) in the World and its Importance in Delivery of Health Care - Farah Asad Mansuri (KARACHI MEDICAL AND DENTAL COLLEGE, 2017)
Inter-professional education is one  of  the  transformations  in  medical  education.  Though  prevalent  more in developed than developing countries for about half a century, but only in the last 10 years has shown an overriding role in various health  related  fields.  Inter-professional  or  collaborative  education was started in order to  improve  health  care  delivery  by  incorporating  better  communication,  team  work, assigning responsibilities to individual providers and observing ethical values in a  health  care  setting, among  providers  of  various  professional  background.  World  Health  Organization  and  other  top rated education agencies have necessitated the role of IPE but with insufficient evidence from dif-   ferent fields of medical practice. The role of IPE has been  determined  in  medical  education,  by  se- lecting work setting, types of professionals, content of the course, data collection procedures and use         of subsequent analysis. Most of the evidence regarding effectiveness of IPE in  actual  collaborative  practice is demonstrated from developed countries. While developing countries basically reported dy- namics of IPE and lack enough evidence in evaluating Inter-Professional Practice (IPP). This review is written in order to identify the global incidence of IPE and particularly that of the devel-   oping world. An attempt has been made to identify the gaps in available literature for its fields of prac-      tice or research techniques applied in IPE and the types of its domains that has been studied.